Contribution of the inflammasome to inflammaging - Nancy H. Mejias; Camila C. Martinez; Marisa E. Stephens; Juan Pablo de Rivero Vaccari (Journal of Inflammation, 2018)
Abstract Background Inflammation is a natural part of the aging process. This process is referred to as inflammaging. Inflammaging has been associated with deleterious outcomes in the aging brain in diseases such as Alzheimer’s disease and Parkinson’s disease. The inflammasome is a multi-protein complex of the innate immune response involved in the activation of caspase-1 and the processing of the inflammatory cytokines interleukin (IL)-1β and IL-18. We have previously shown that the inflammasome plays a role in the aging process in the brain. In this study, we analyzed the brain of young (3 months old) and aged (18 months old) mice for the expression of inflammasome proteins. Results Our findings indicate that the inflammasome proteins NLRC4, caspase-1, apoptosis-associated speck-like protein containing a caspase recruitment domain (ASC), and IL-18 are elevated in the cytosol of cortical lysates in aged mice when compared to young. In addition, in the cytosolic fraction of hippocampal lysates in aged mice, we found an increase in NLRC4, caspase-1, caspase-11, ASC and IL-1β. Moreover, we found higher levels of ASC in the mitochondrial fraction of aged mice when compared to young, consistent with higher levels of the substrate of pyroptosis gasdermin-D (GSDM-D) and increased pyroptosome formation (ASC oligomerization). Importantly, in this study we obtained fibroblasts from a subject that donated his cells at three different ages (49, 52 and 64 years old (y/o)) and found that the protein levels of caspase-1 and ASC were higher at 64 than at 52 y/o. In addition, the 52 y/o cells were more susceptible to oxidative stress as determined by lactose dehydrogenase (LDH) release levels. However, this response was ameliorated by inhibition of the inflammasome with Ac-Tyr-Val-Ala-Asp-Chloromethylketone (Ac-YVAD-CMK). In addition, we found that the protein levels of ASC and IL-18 are elevated in the serum of subjects over the age of 45 y/o when compared to younger subjects, and that ASC was higher in Caucasians than Blacks and Hispanics, whereas IL-18 was higher in Caucasians than in blacks, regardless of age. Conclusions Taken together, our data indicate that the inflammasome contributes to inflammaging and that the inflammasome-mediated cell death mechanism of pyroptosis contributes to cell demise in the aging brain.